Evolution of the aggressive or scaling character of the water according to the dose of corrosion inhibitor - Mbayo Kyongo Longo, Jerry; Mbuyu Ilunga, Eddy; Wa Banza Bonaventure, Banza; Kanda, Jean-Marie (International Journal of Advanced Chemistry, 2019)
In the treatment of water to fight against corrosion, there are several techniques that can slow down this phenomenon and thus extend the service life of the pipes. Among these techniques, the use of corrosion inhibitors is one of them. It is in this context that the evolution of the aggressive and turbulent nature of the water of the Lubumbashi River has been studied experimentally through the determination of indicators such as pH, chemical potential, total alkalimetric titre, calcium hardness THCa, free chlorine content, dissolved oxygen content, SO42- sulfate ion content and Ryznard and Langelier index. Numerous relationships between the dose of the inhibitor and the physicochemical parameters of water have been established. Similarly, it has also been shown that the dose variation of the inhibitor is related to the Langelier index and the Ryznard index. Thus, it follows that with the dose of 0.30ml / L, an appreciable decrease in dissolved oxygen, which is the main oxidant in basic medium, is recorded. The use of the inhibitor has a positive effect on corrosion because it acts directly on all physicochemical parameters and on all oxidants. Subject to economic analyzes, the dose of 0.30 ml / L is more advisable especially as it would prevent in the cooling circuit degradation of the thermal coefficient and the formation of precipitates in the exchangers occasioned. Â Â